Nomenclatural changes in Neotropical Eulophidae, Eupelmidae and Torymidae (Hymenoptera: Chalcidoidea) relating to parasitoids of Cecidoses eremita (Lepidoptera: Cecidosidae) - Burks, R. A.; Gibson, G. A.p.; la Salle, J. (Zootaxa, 2005)
Two monospecific genera described by Brèthes (1927) in Eulophidae are newly synonymized under genera in Torymidae and Eupelmidae; respectively, Parasympiesis Brèthes is recognized as a junior synonym of Torymus Dalman n. syn. and Tropimius Brèthes as a junior synonym of Brasema Cameron n. syn. Torymus cecidicolus (Brèthes) n. comb. and Brasema willei (Brèthes) n. comb.  are rediagnosed, and Torymus alegrensis (Brèthes) n. syn. is recognized as a junior synonym of T. cecidicolus. All three species were described as parasitoids of the gall-forming lepidopteran, Cecidoses eremita Curtis (Cecidosidae). Brasema willei is one of 11 species of Brasema described from South America, including B. acauda (Ashmead) n. comb., B. aprilis (Ashmead) n. comb., B. basicuprea (Walker) n. comb., B. chapadae (Ashmead) n. comb., B. corumbae (Ashmead) n. comb., B. peruviana (Crawford) n. comb., and B. proxima (Ashmead) n. comb. from Eupelmus Dalman, and B. cyanea (Ashmead) n. comb. from Zaischnopsis Ashmead.